Cannabinoids and Myocardial Ischemia: Novel insights, Updated Mechanisms, and Implications for Myocardial Infarction - Seif El Dahan, Karim; Machtoub, Dima; Massoud, Gaelle; Nasser, Suzanne A.; Hamam, Bassam; Kobeissy, Firas; Zouein, Fouad A.; Eid, Ali H. (Current Medicinal Chemistry, 2022)
Cannabis is the most widely trafficked and abused illicit drug due to its calming psychoactive properties. It has been increasingly recognized as having potential health benefits and relatively less adverse health effects as compared to other illicit drugs; however, growing evidence clearly indicates that cannabis is associated with considerable adverse cardiovascular events. Recent studies have linked cannabis use to myocardial infarction (MI); yet, very little is known about the underlying mechanisms. A MI is a cardiovascular disease characterized by a mismatch in the oxygen supply and demand of the heart, resulting in ischemia and subsequent necrosis of the myocardium. Since cannabis is increasingly being considered a risk factor for MI, there is a growing need for better appreciating its potential health benefits and consequences. Here, we discuss the cellular mechanisms of cannabis that lead to an increased risk of MI. We provide a thorough and critical analysis of cannabinoids’ actions, which include modulation of adipocyte biology, regional fat distribution, and atherosclerosis, as well as precipitation of hemodynamic stressors relevant in the setting of a MI. By critically dissecting the modulation of signaling pathways in multiple cell types, this paper highlights the mechanisms through which cannabis may trigger life-threatening cardiovascular events. This then provides a framework for future pharmacological studies which can identify targets or develop drugs that modulate cannabis’ effects on the cardiovascular system as well as other organ systems. Cannabis’ impact on the autonomic outflow, vascular smooth muscle cells, myocardium, cortisol levels and other hemodynamic changes are also mechanistically reviewed.
Keywords: endocannabinoid system